2020
DOI: 10.1186/s40677-020-0144-6
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between seepage water volume and total suspended solids of landslide dam failure caused by seepage: an experimental investigation

Abstract: Background Landslide dams inevitably demonstrate the potential for catastrophic failure with high-risk damage to life and property at the downstream site. Hence, knowledge of the internal stability of dam materials is a key to predicting the seepage failure of landslide dams. In this study, experiments were conducted to examine the relationship between seepage volume and total suspended solids (TSS) of seepage water based on hydro mechanical constrains. Understanding the relationship between the seepage volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Studies found that water flows positively influenced the TSS distribution in water bodies. A study by Dhungana & Wang (2020) confirmed that the flow rate increases the TSS concentration and eventually permits dam failure. TSS content in the water bodies, especially in lower drainage basins, is highly responsive to variations in flow rate (López et al, 2021).…”
Section: Possible Factors Affecting Spatiotemporal Variation Of Tss D...mentioning
confidence: 89%
See 1 more Smart Citation
“…Studies found that water flows positively influenced the TSS distribution in water bodies. A study by Dhungana & Wang (2020) confirmed that the flow rate increases the TSS concentration and eventually permits dam failure. TSS content in the water bodies, especially in lower drainage basins, is highly responsive to variations in flow rate (López et al, 2021).…”
Section: Possible Factors Affecting Spatiotemporal Variation Of Tss D...mentioning
confidence: 89%
“…In recent years, several studies have focused on the possible factors affecting the spatiotemporal variation of total suspended solids distribution in water bodies. Factors affecting the spatiotemporal distribution of TSS in river bodies are water flow rate, salinity, tidal movement and anthropogenic activities (Che Ali et al, 2020;Che Ngah et al, 2012;Dhungana & Wang, 2020;Håkanson, 2006;Rossi et al, 2006).…”
Section: Possible Factors Affecting Spatiotemporal Variation Of Tss D...mentioning
confidence: 99%
“…This kind of subsidence is similar to backward erosion and the failure point develops from the downstream slope to the dam crest. The dam material composed of fine particles can reduce the void ratio and improve the impermeability of the dam (Dhungana and Wang, 2020). Compared with Figure 9A, the dam in Figure 9E has experienced a complete overtopping breach process.…”
Section: Breach Morphology Evolution Processes Of Landslide Dam Along the Longitudinal Directionmentioning
confidence: 99%
“…Based on case studies (Rico et As pointed out by Vogel (2013), due to numerous TSF failures worldwide, there were almost 2400 fatalities between 1961 and 2020 (Owen, 2020; WISE, 2019), and we may expect that in the next few years, along with the increase of tailing production, this number will further increase (NRGI, 2017, Owen, 2020). There are numerous possible reasons for such a situation like the continuous expansion of dam volume due to the facility development, an increase of tailings and seepage volume (Dhungana, 2020) or intensification of extreme rainfall occurrence due to climate change (Myhre et al, 2019). On the other hand, in some cases, the exact reasons are unknown, which could lead to the conclusion that some mistakes have been made during the facility project and development or risk evaluation.…”
Section: Introductionmentioning
confidence: 99%